#### Answer

$\frac{63}{10}=-6\frac{3}{10}$

#### Work Step by Step

$ab=(-7)(\frac{9}{10})=-\frac{7\times9}{10}=-\frac{63}{10}=-6\frac{3}{10}$

Published by
Pearson

ISBN 10:
0321955048

ISBN 13:
978-0-32195-504-3

$\frac{63}{10}=-6\frac{3}{10}$

$ab=(-7)(\frac{9}{10})=-\frac{7\times9}{10}=-\frac{63}{10}=-6\frac{3}{10}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.